Pengaruh Teknologi, Modal, dan Tenaga Kerja Terhadap Produksi dan Pendapatan UMKM Kerajinan Ukiran Kayu di Kabupaten Gianyar - Gusti Putu Agung Krisna Mahendra, I; Ketut Ayuningsasi, Anak Agung (Public Service and Governance Journal, 2024)
The purpose of this study aims to analyze the influence of technology, capital, and labor on production in woodcarving handicraft SMEs in Gianyar Regency. To analyze the effect of technology, capital, labor, and production on the income of MSMEs in woodcarving crafts in Gianyar Regency. To analyze the indirect effect of technology, capital, and labor on income through production in woodcarving MSMEs in the approach used in this study is an associative quantitative approach. This research was conducted in Gianyar Regency with an analytical technique, namely path analysis. The results of this study are that technology and labor have a direct positive but not significant effect on the production of MSME woodcarving crafts in Gianyar Regency, while capital has a direct positive and significant effect on the production of MSME woodcarving crafts in Gianyar Regency. Technology directly has a positive but not significant effect on income, labor directly has a negative but not significant effect on income while capital and production have a direct positive and significant effect on the income of MSMEs in woodcarving crafts in Gianyar Regency. Technology, capital, and labor do not have a significant effect on income indirectly through the production of woodcarving handicraft SMEs in Gianyar Regency.